Connecting and Attuning Mental Health Care for Adolescent Patients: The Role of Presence Practice - Precious Chibuike Chukwuere PhD (SAGE Publishing, 2023)
Introduction The healthcare system over the years has witnessed evolvement and transformation in the care pattern, including in the mental healthcare system. This has seen a considerable and commendable improvement in patient care. This article aims to demonstrate the need for "presence practice" and practical implications thereof, in the care of adolescents with mental health illnesses and to further demonstrate the need for connecting and attuning mental health care for good care and positive nurse and patient outcomes. The developmental stage of adolescents is characterized by various psychosocial changes. At the same time, the emergence of numerous mental health conditions is prevalent at the adolescent stage, contributing to the disease burden among this age group. Understandably, the prevalence of mental health illnesses in adolescents could be associated with their vulnerability and the result of the interaction of numerous biopsychosocial factors in the lives of the individuals, asserting influences on their development and mental health such as family challenges, the stress associated with schooling, relationship issues, and abuse. Method This article follows a quality improvement method where the author took time to nonsystematically explain existing literature on presence practice and its practical implication and further practically demonstrated the need for and how to facilitate connecting and attuning mental health care for good care and positive nurse and patient outcomes. Result Presence practice should be adopted by mental health nurses to foster the establishment of relational care with mental health care users, such as adolescents with mental illness, and to help mitigate relapse. Being open-minded and preparing their minds to be receptive and present during care should be part of nurses effective presence practice. Conclusion The article concludes that mental health nurses, as frontline caregivers, should always endeavor to connect and attune care to the needs of the adolescents receiving mental health care to foster positive outcomes.